The very-rapid and the ultra-rapid virologic response to two treatment options in patients with chronic hepatitis C: an interim report of a prospective randomized comparative effectiveness study - Yakoot M; Abdo AM; Yousry A; Helmy S (Dove Medical Press, 2015)
Mostafa Yakoot,1,2 Alaa M Abdo,3 Ahmed Yousry,4,5 Sherine Helmy61Green Clinic and Research Center, 2Abbas Helmy Clinics, 3Tropical Medicine and Hepatology Department, Alexandria Faculty of Medicine, Alexandria University, 4Microbiology Department, High Institute of Public Health, Alexandria University, 5Mabarat El Asafra Labs, 6Pharco Corporation, Alexandria, EgyptBackground: We aimed in this interim report to compare two registered generic sofosbuvir products for the degree and speed of virologic response to a dual antiviral treatment protocol within the first 2 weeks of treatment.Methods: Data collected during the period of this interim report from the first 25 patients randomized to either one of two generic sofosbuvir products (Grateziano or Gratisovir) at a daily dose of one 400 mg tablet plus a weight-based ribavirin dose were analyzed for both the degree and speed of virus load reduction at the end of 1 and 2 weeks from starting treatment.Results: The baseline Log10 transformed virus load (Log polymerase chain reaction) showed a fairly similar marked and significant reduction in both groups by more than 4 and 5 Logs at the end of week 1 and 2 of starting treatment, respectively. The differences between the two treatment groups at both analysis points were not statistically significant (P>0.05) by repeated measures factorial analysis of variance test. The differences in proportions of patients with ultra-rapid virologic response at the end of week 1 and very-rapid virologic response at the end of week 2 in both groups were also not statistically significant (P>0.05).Conclusion: We can conclude from this interim report that the two generic products Gratisovir and Grateziano are almost equally fast and efficacious in reducing the hepatitis C virus load in our study setting.Keywords: chronic hepatitis C, dual antiviral therapy, ultra-rapid virologic response, very-rapid virologic response, direct acting antiviral agents